Answer:
4x + 1
Step-by-step explanation:
note that (f + g)(x) = f(x) + g(x) , thus
f(x) + g(x)
= x + 3x + 1 ← collect like terms
= 4x + 1
together = add
add the fractions
3 7/10 + 5 9/10
add the whole numbers first
3+5=8
add the fractions
7/10+9/10= 16/10
8 16/10
reduce 16/10 divide by 2
16/2= 8
10/2= 5
8 8/5
whole number changes to 9
8-5=3
denominator stays the same
9 3/5
Answer:
9 3/5
-3.6
Explaination: it goes through the 6 and -3 points in the slope.
1/7 of 42 is smaller. 47/7= 6 < 18 = 36/2
Answer:
sry I can't understand how to do this question